MAPPING CONSTRUCTION OF SOIL VARIABILITY WITHIN THE LANDSCAPE - M. Edi Armanto (Direktorat Sumber Daya Akademik dan Perpustakaan, 2002)
The research aimed to construct mapping soil variability within the landscape.The research was located in Central Lampung (308 ha). The survey type wasdetailed using topographic maps (scales of 1:5,000) and the aerial photointerpretations. The soil samples were performed by soil pits and borings forwhole survey area (1 composite sample/ha), classified and analyzed. Thebalancing methods used transect diagrams, delineated soil bodies and area pointstatistics. The research resulted that the aerial photo interpretation was a veryuseful method to delineate soil units on the map. A combination of aerialimagery, topographical maps and field observations provide the most effectiveapproach for soil mapping in complex landscapes with simple soil patterns.Although the soil sampling was carried out relatively systematic according torelief form and the driving lanes of tractors, there was some agreement betweenpoint statistics and map data. The difference between both methods wasmaximally 3 %. The result combination from both methods shows that 60 % ofthe landscape was classified as eroded, 35 % as normal and 5 % as colluviated.There was no balance of erosion and onsite sedimentation.Keywords : Construction, landscape, mapping, soil variability